PENGARUH MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA PEMBELAJARAN KOMIK DIGITAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA TERPADU KELAS VIII SMP NEGERI MANDALA RAIMANUK TAHUN AJARAN 2018/2019 - Viktoria Isa; Agus Maramba Meha; Melkias Manggoa (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
The purpose of this study was to determine the effect of role playing learning models assisted by digital comic learning media on student learning outcomes. The method used is quasi experiment. The research design used was posttest only control design. Data collection techniques using the Learning Outcomes Test. Data management and analysis using the polled variance t-test formula with SPSS version 16 statistical test. Based on the results of data analysis, it shows that there is a significant effect with tcount greater than ttable, 6.488> 1.674, it can be concluded that H1 is accepted and H0 is rejected, meaning there is a significant influence in the use of role playing learning models assisted by digital comic learning media towards student learning outcomes.